Komunikasi Orang Tua-Anak Dalam Mengajarkan Rasa Kasih Sayang dan Kesejahteraan Keluarga - Handayani, S.W.E. (Responsibilitas, 2010)
Abstract Communications in family stands is vital in psychological development of child. Area of closest in forming bottom characte child of as stock in facing situation of external environment of home in this case hardly influences behavior of child. Area which can print development of growth of child. High intensity and accompanied with high frequency hence big possibility that his(its happened attitude change is followed with an action. So if old fellow and child Â of having equality scope in experience of and cognition will facilitate people to takae certainty about form of message submitted. Thereby communications earns effective and is fluent. Explains that communications between old fellows (father and mother) with its(the child is followed frequently they are interaction of its(the intention in the relationship can be each other influence influences. Keyword : komunikasi keluarga, kesejahteraan